The island of excess love - Block, Francesca Lia 1962- (Henry Holt, 2014)
Pen, Hex, Ash, Ez, and Venice are living on hard work, companionship, and dreams in the pink house by the sea until a foreboding ship arrives and all start having strange visions of destruction and violence then, trance-like, they head for the ship and their new battles, with Pen using Virgil's epic Aeneid as her guide
Companion to: Block, Francesca Lia: Love in the Time of Global Warming
Keywords: Virgil; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Social Issues / Adolescence; JUVENILE FICTION / Family / Orphans & Foster Homes; JUVENILE FICTION / Legends, Myths, Fables / Greek & Roman; JUVENILE FICTION / Love & Romance; Survival; Friendship; Love; Visions; Science fiction; Los Angeles (Calif.); Jugendbuch